DYNAMIC GOVERNANCE BASED EDUCATIONAL TOURISM DEVELOPMENT MODEL IN INDONESIA - Anwar, Muhammad Khairul; Zauhar, Soesilo; Wanusmawatie, Ike (Faculty of Administrative Science, Universitas Brawijaya, 2023)
Educational tourism has dynamic developments, as well as problems that change along with global developments, including in Indonesia. It is important to develop educational tourism as an effort to provide learning to the public, and especially school students. The aim of this research is to identify the development of educational tourism in Indonesia, as well as to formulate a policy implementation model in Indonesia. This research uses qualitative methods with discourse network analysis. Data sources were obtained from cyberspace in the form of mass media and trusted articles. Based on the results of the analysis, the results showed that there were 5 actors that could be photographed, namely non-governmental organizations, academics, government, public and private sectors. The five actors expressed several opinions regarding the 9 key issues in this research, namely nature education, innovation, education tourism development, infrastructure, human resources, facilities, technology, history and stakeholders. From the results of these variables, a policy recommendation model was formed which was moderated by the concept of dynamic governance, namely thinking ahead, thinking again, and thinking across.